Remexa minhas entranhas: poéticas de um feminino monstruoso - Aniceto, Lara Nicolau (2018)
In search of other possibilities of subjectivation, I try to materialize the monster woman, in a poetic practice that overflows the boundaries between art and life. Record a study on the condition of women in a patriarchal order, where it is commonly located in place of ‘other’, ‘abject’, the border of a nonhuman being. Through my repertoire of experiences of this ‘other’ place and the assimilation of images present in magical tales, a path is drawn that converges in a performance guided by feminism and the shared and incorporated experience of the sensitive. It is essential to understand a moment that is a historical moment of hatred and extermination of women: the ‘witch hunt’ undertaken in the Middle Ages, to arrive at notions of counter-production of gender oppression in a realm where the performative and the performative are found in the feminist art movement that began in the late 1960s. Alongside some performers who made the body the vehicle for their speech, I place myself. The creative process developed throughout this intuitive, affective and personal research, but also with a sense of interference and political noise, presents the Monster Woman Manifesto and the collection of intersections between theories about the body and collective sensory practices, weaving the place where my naked body is the center of experience and subjectivation. The monster woman declares her faults and exposes her viscera so that the public crosses him, mold, and by stirring her bowels, she undoes herself, to create herself again in another existential landscape.